Marine propellers and propulsion - Carlton, J. S. (Elsevier Butterworth-Heinemann, 2007)
Although the propeller lies submerged out of sight, it is a complex component in both the hydrodynamic and structural sense. Marine Propellers and Propulsion fulfils the need for a comprehensive and cutting edge volume that brings together a great range of knowledge on propulsion technology, a multi-disciplinary and international subject. The book comprises three main sections covering hydrodynamics; materials and mechanical considerations; and design, operation and performance. The discussion relates theory to practical problems of design, analysis and operational economy, and is supported by extensive design information, operational detail and tabulated data. Fully updated and revised to cover the latest advances in the field, the new edition now also includes four new chapters on azimuthing and podded propulsors, propeller-rudder interaction, high-speed propellers, and propeller-ice interaction. The most complete book available on marine propellers, fully updated and revised, with four new chapters on azimuthing and podded propulsors, propeller-rudder interaction, high-speed propellers, and propeller-ice interaction A valuable reference for marine engineers and naval architects gathering together the subject of propulsion technology, in both theory and practice, over the last forty years Written by a leading expert on propeller technology, essential for students of propulsion and hydrodynamics, complete with online worked examples.